Multicultural Education as a Means of Strengthening Social Skills in a Heterogeneous Society - Nurhaswinda Nurhaswinda (Journal of Humanities, Social Sciences, and Education, 2025)
Multicultural education plays a crucial role in developing students' social skills, especially in heterogeneous societies. This article aims to examine how multicultural education can serve as a means of enhancing social skills through a literature study. The findings indicate that a multicultural approach in education helps students understand, appreciate, and interact with the cultural diversity around them. Through collaborative learning strategies, reflective discussions, and experience-based approaches, social skills such as empathy, effective communication, and cooperation can be improved. The study reveals that multicultural education not only enriches cultural awareness but also strengthens harmonious social interactions in diverse societies. Therefore, multicultural education needs to be systematically integrated into the curriculum to prepare individuals with social awareness who can adapt to a diverse environment.